Inter-segment coordination of male and female collegiate ice hockey players during forward skating starts - Mazurek, C. M.; Pearsall, D. J.; Renaud, P. J.; Robbins, S. M. (Research Quarterly for Exercise and Sport, 2024)
Purpose Coordination in ice hockey skating has been minimally investigated, particularly in females. The objective was to compare lower-extremity inter-segment coordination of collegiate male and female ice hockey players during forward skating starts.